2022
DOI: 10.1021/acsfoodscitech.1c00442
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Chemical and Physical Stability of Mayonnaise Prepared from Enzymatically Interesterified Corn Oil-Based Designer Lipids

Abstract: The objective of current work is to study the physicochemical stability of mayonnaise made from corn oil designer lipid (CODL) and to evaluate the performance of monocaprylin/dicaprylin (80:20) (MD82) as an emulsifier. The oxidative stability, texture, microstructure, and rheological characteristics of CODL-based mayonnaise are evaluated and compared with those of the commercial sample. CODL-based mayonnaise showed good oxidative stability compared to the commercial sample based on established data of acid val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Moreover, the PV of mayonnaise was unchanged as compared to that of the OB; specifically, the PV was 2.0 and 1.9 meqO 2 /Kg in the freshly prepared AV-May and OLV-May, respectively. According to the recent work of Jadhav et al (2022) [ 42 ], homogenization treatment and other ingredients did not trigger any auto-oxidation reactions in the formulated mayonnaises.…”
Section: Resultsmentioning
confidence: 94%
“…Moreover, the PV of mayonnaise was unchanged as compared to that of the OB; specifically, the PV was 2.0 and 1.9 meqO 2 /Kg in the freshly prepared AV-May and OLV-May, respectively. According to the recent work of Jadhav et al (2022) [ 42 ], homogenization treatment and other ingredients did not trigger any auto-oxidation reactions in the formulated mayonnaises.…”
Section: Resultsmentioning
confidence: 94%
“…In general, the use of resveratrol as natural antioxidants prevents lipid oxidation in mayonnaise during storage, and lipid nanocarriers can be a suitable system for encapsulating resveratrol to preserve its antioxidant properties. In another research, corn oil designer lipid‐based mayonnaise showed considerable oxidative stability compared with the control samples based on recorded data from acid value, peroxide value, p‐anisidine value, and TOTOX value (Jadhav et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Firmness is the maximum compression that is related to the intensity of emulsification, in which high intensity yields high firmness (Olsson et al, 2018). Consistency of mayonnaise is defined as the average of the entire area under the positive curve, which can be attributed to the balance of interparticle colloidal forces as indication of fluid viscosity (Jadhav et al, 2022; Primacella et al, 2019). Cohesiveness is determined as the maximum force in the negative area of curve that is taken as an indication of the stickiness of the mayonnaise.…”
Section: Resultsmentioning
confidence: 99%